Od substancji do funkcji. Ernst Cassirer i pojęcie idealizacji - Borbone, Giacomo (Człowiek i Społeczeństwo, 2016)
The German philosopher Ernst Cassirer is well known for his masterful historical works on modern philosophy and also for his philosophy of symbolic forms, but there is an aspect that has been disregarded by those scholars who dedicated several books and essays to Cassirer’s thought, I mean the difference between abstraction and idealization. The philosopher who, for the first time, developed systematically this topic in the field of epistemology was the Polish philosopher Leszek Nowak, but nonetheless, there are philosophical and epistemological works where we can find a very clear analysis of the difference existing between abstraction and idealization and, in this respect, the works of the German philosopher Ernst Cassirer are quite emblematic. It is very difficult to find in the literature on Cassirer some explicit analysis on this topic, so in this essay I will try, through Nowak’s conceptual apparatus, to explain the formation of scientific concepts in Cassirer’s view (especially by taking into account Cassirer’s critique of abstraction).